Methods and Means of Increasing the Efficiency of Using Modern Pedagogical Technologies in English Classes - Ismoilava, Sevara (Research Parks Publishers, 2023)
The use of various educational technologies in pedagogical activity allows teachers and other specialists to increase the motivation of students, the professional and practical orientation of classes, and, consequently, to achieve more guaranteed planned results in their professional and pedagogical activities. The article deals with the issues based on using different methods in increasing the efficiency of using modern pedagogical technologies in English classes.